2015
DOI: 10.1149/2.0261508jes
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of LiNi0.5Mn1.5O4Positive Composite Electrodes with Industry-Relevant Surface Capacities for Lithium Ion-Cells

Abstract: Influence of the electrode formulation on the cyclability of LiNi 0.5 Mn 1.5 O 4 was studied for industry-relevant surface capacities (i.e. up to ∼3 mAh cm −2 ) with two mixing methods at the lab scale: ball milling and magnetic stirring. The inactive binder and carbon additives content were varied, as well as the type of those. A more homogeneous distribution of additives is observed in ball milled electrodes compared to stirred ones. The cycle life of the former is degraded with lower coulombic efficiency at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Graphite‐composite electrodes featuring 90 wt % graphite (SLP 30, Imerys), 5 wt % Super C45 (C45, Imerys), and 5 wt % CMC binder were prepared by a pre‐pilot automated coated line, as shown in Ref. . Disk electrodes (1.13 cm 2 geometric area) with a mass loading of active material in the range of 3.0–4.0 mg cm −2 (ca.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphite‐composite electrodes featuring 90 wt % graphite (SLP 30, Imerys), 5 wt % Super C45 (C45, Imerys), and 5 wt % CMC binder were prepared by a pre‐pilot automated coated line, as shown in Ref. . Disk electrodes (1.13 cm 2 geometric area) with a mass loading of active material in the range of 3.0–4.0 mg cm −2 (ca.…”
Section: Methodsmentioning
confidence: 99%
“…tective film formed on the cathode surface andt he better dispersion of composite-electrode components than in those made with PVdF should reduce the contact between LNMO and electrolyte, thus effectively suppressing Ni and Mn dissolution over 100 cycles even at high temperature. [7] Nguyen et al [8] reported that aqueous processed LNMO electrodes with CMC binder showedp oorer cycling performance than those with PVdF binderi nE C/DMC-1 m LiPF 6 owing to the presence of trace impurities of water in the composite electrodes that can lead to HF formation, whichi sd etrimental for the electrode's cycling performance. The electrode-drying step crucially affects the electrochemical performance of made-in-water LNMO electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…22 As for LFP, the main reasons for such improved performance were identified to be the well maintained electrode microstructure, a lower internal resistance and faster de-/lithiation kinetics, a higher peeling strength, and less swelling of the binder by the liquid organic electrolyte, 162,[164][165][166] while the proper drying of in-waterprocessed electrodes is apparently crucial. 18,170 Once more, the use of PAA was reported to result in the formation of a very homogeneous surface coating of the active material particles, 169 which is, in light of the high lithium de-/insertion potential of LNMO and the rather limited oxidative stability of common organic-carbonate-based electrolytes, of even greater relevance compared to LFP and LMO, since it turned out to stabilize the electrode/electrolyte interface, thus preventing or at least lowering the continuous electrolyte decomposition. Another very interesting aspect of the study of Pieczonka et al 169 was that the therein utilized Li-PAA may also as a Li + reservoir, which simultaneously allows for buffering the acidity of the electrolyte due to the corresponding exchange of lithium cations (from the binder) and protons (from the electrolyte), which mitigates parasitic side reactions at the interface.…”
Section: Reviewmentioning
confidence: 99%
“…In contrast, the reduced cycle life of the LNMO_comm electrodes can be assigned to the following factors: low electroactive material density, loss of contact of the different electrode components, and the detrimental effect of parasitic reactions of the electrode additives, as, for example, electrolyte reactions with carbon particles. [ 50 ] This latter effect is avoided in the case of LNMO thin‐films that are 100% electroactive material.…”
Section: Resultsmentioning
confidence: 99%